INFLUENCE OF TRADITIONAL MARKETS ON COMMUNITY ECONOMIC IMPROVEMENT (STUDY OF TRADITIONAL SENEN MARKET IN MEREMPAN HULU VILLAGE SIAK DISTRICT, SIAK REGENCY) - Nurhadi Nurhadi; Holy Hardiana (Universitas Negeri Medan, 2021)
This study aims to determine the effect of traditional markets on improving the community's economy. The study used a descriptive quantitative approach.SThe sample used a random sampling method with a total of 83 respondents, consisting of 39 traders, 24 farmers, 12 fishermen and 8 IRT.Techniques for analyzing product moment correlations coefficient data using SPSS 20.0 program tools. Collecting data by observation, questionnaires and documentation.Primary data were processed using validity and reliability tests, simple linear regression analysis, correlation tests, hypothesis testing (t test), and coefficient of determination (R square). From the results of the linear regression test, there is a positive influence andsThe significance of the traditional market of Kampung Merempan Hulu towards improving the community's economy, this is because it is (6,389 > 1,990). While the significance level is 0.000 <0.05, which means it is significant, then Ho is rejected and Ha is accepted. With a coefficient value of 0.579, it is in the interval 0.40-0.599, which means that the traditional market of Kampung Merempan Hulu is quite strong in influencing the economic improvement of the community.